Macerie: il fantasma della natura nell’era dell’Antropocene (Glocalism: Journal of Culture, Politics and Innovation, 2018)
The blind faith in progress, as a submission to a nomosimbued with mythical elements, is declined today through concepts and slogans which participate in the umpteenth ideological mystification of the technocratic society of consumption, aimed at legitimizing and justifying the unconditional domination and exploitation of Nature, even through the (wholly fraudulent) promotion of its protection. The present paper intends to show how even such escamotages, far from breaking the logic of “growth for growth”, move rather in the direction of what Löwith called a total denaturalization of the world and man, that is to say the triumph of the Apparatenweltof Günther Anders. If Man interacts with the natural environment solely through the mediation of a variegated set of techniques, in fact, Nature itself disappears from its subjective horizon and he does nothing but interact with these techniques and with the techno-nature which they originate.
Keywords: techno-nature; eco-sophy; augmented reality; ethics; Anthropocene